Analisis Vegetasi Tanaman Koleksi Pada Blok Perlindungan Taman Hutan Raya Bunder Yogyakarta: Analysis Vegetation of Plant Collections in the Protection Block at Bunder Grand Forest Park Yogyakarta - Joya Anggita Cahya; Ana Agustina; Ike Nurjuita Nayasilana; Ita Mirrotul Tsaqila; Galuh Masyitoh (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2024)
Fundamental information about stands, particularly concerning structural diversity and composition, is crucial for comprehending the extent of plant species variety. This study is to analyze the structure and composition of species within the plant collection stands located in the protected area of Bunder Forest Park in Yogyakarta. The research efforts encompass the gathering of data on growth parameters like height, diameter, and crown width. The vegetation analysis data collection method entailed establishing observation plots in both square and transect configurations, each measuring 100 meters in length. The determined sample intensity was 3.3%, yielding 15 plots distributed over 3 transects, each measuring 100×20 meters. The plant species composition in plots 20 and 21 of the protection block in Tahura Bunder comprises 10 species: flamboyant, cajuputy, nyamplung, acacia, mahogany, teak, trembesi, gamal, jambu darsono, and tamarind. Transect 3 exhibited the greatest species variety. The vegetation structure in plots 20 and 21 is categorized within layers C and D. The main tree species in the stand, according to the Importance Value Index (IVI), is cajuputi (Melaleuca leucadendra), with an IVI of 208.27%. This study recommends enhancing plant species diversity to ensure the sustainability of genetic resources, particularly the indigenous species in the Tahura Bunder Yogyakarta region.